2020
DOI: 10.1016/j.cbi.2019.108900
|View full text |Cite
|
Sign up to set email alerts
|

Predictive early gene signature during mouse Bhas 42 cell transformation induced by synthetic amorphous silica nanoparticles

Abstract: Highlights • Synthetic amorphous silica nanomaterials induce transformation of Bhas 42 cells • Early modulated signaling pathways are linked to cell adhesion and proliferation • Twelve genes were selected based on their potential role in cell transformation • These genes may serve as early markers of Bhas 42 cell transformation induced by SAS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…A concentration-dependent increase in cell transformation ability was demonstrated in Balb/c 3T3 [41] and Caco-2 cells [43], as well as induced malignancies in BEAS-2B cells exposed to Ag-NP [42]. Synthetic amorphous silica nanoparticle (SAS) (NM-200, nm-201, nm-202, and nm-203)-exposed Bhas 42 cell transformation model showed concentration dependency [45,46]. Only the highest concentration (20 µg/mL) showed significant cell transformation ability in TiO 2 -NP (NM102)-exposed BEAS-2B cells [54].…”
Section: Exposure Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A concentration-dependent increase in cell transformation ability was demonstrated in Balb/c 3T3 [41] and Caco-2 cells [43], as well as induced malignancies in BEAS-2B cells exposed to Ag-NP [42]. Synthetic amorphous silica nanoparticle (SAS) (NM-200, nm-201, nm-202, and nm-203)-exposed Bhas 42 cell transformation model showed concentration dependency [45,46]. Only the highest concentration (20 µg/mL) showed significant cell transformation ability in TiO 2 -NP (NM102)-exposed BEAS-2B cells [54].…”
Section: Exposure Concentrationsmentioning
confidence: 99%
“…Size-dependent cell transformation was observed when the HBEC-3KT cell line was exposed to the TiO 2 -NP and MWCNT with a smaller diameter but not to that with a larger diameter, in the soft-agar colony formation assay [57]. SAS (NM-200 and nm-201, nm-202 and nm-203) were reported as tumor-promoter substances in the Bhas 42 cell transformation model, and a marked size-dependency was apparent, in which a higher the particle size indicated a higher transformation ability [45]. In a comparison between coated (either with citrate or silica) vs. uncoated TiO 2 -NP and ZrO 2 NP, it was shown that coating with silica seems to prevent Balb/3T3 morphological transformation induced by ZrO 2 NP [58].…”
Section: The Influence Of Physicochemical Properties Of Nms In Cell T...mentioning
confidence: 99%
“…Recently, in vitro and in vivo models were utilized to demonstrate that silica NPs in Xuanwei bituminous coal may play an important role in the development of lung cancer by inducing inflammation (Li et al, 2019). More recently, it was found that genes related to the early stage of cell transformation induced by silica NPs are related to cancer progression (Kirsch et al, 2020).…”
Section: Nano‐metal Oxidesmentioning
confidence: 99%